2020
DOI: 10.3390/ijms21155351
|View full text |Cite
|
Sign up to set email alerts
|

NMR Characterization of Conformational Interconversions of Lys48-Linked Ubiquitin Chains

Abstract: Ubiquitin (Ub) molecules can be enzymatically connected through a specific isopeptide linkage, thereby mediating various cellular processes by binding to Ub-interacting proteins through their hydrophobic surfaces. The Lys48-linked Ub chains, which serve as tags for proteasomal degradation, undergo conformational interconversions between open and closed states, in which the hydrophobic surfaces are exposed and shielded, respectively. Here, we provide a quantitative view of such dynamic processes of Lys48-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We have developed an NMR technique to quantitatively determine the conformational distributions of Ub chains [ 12 , 13 ]. In this approach, we use monomeric Ub (monoUb) and a cyclic form of Lys48 di-Ub (c-diUb), in which the two Ub units are connected through two isopeptide linkages, as imitations of open and closed states regarding exposure of the hydrophobic surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have developed an NMR technique to quantitatively determine the conformational distributions of Ub chains [ 12 , 13 ]. In this approach, we use monomeric Ub (monoUb) and a cyclic form of Lys48 di-Ub (c-diUb), in which the two Ub units are connected through two isopeptide linkages, as imitations of open and closed states regarding exposure of the hydrophobic surface.…”
Section: Resultsmentioning
confidence: 99%
“…In triUb, the hydrophobic surface of the central Ub unit (Ub2) is competitively shared by the most distal and most proximal Ub units (Ub1 and Ub3, respectively). Our prior NMR analysis indicated that, among the three Ub units of triUb, Ub1 is the one most inclined to expose its hydrophobic surface [ 13 ]. Therefore, if one could improve the intramolecular interaction between Ub1 and Ub2 in triUb, this would facilitate the exposure of the hydrophobic surface of the excluded Ub3 unit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…E3 ubiquitin ligases, the most abundant eukaryotic proteins (Mazzucotelli et al 2006 ; Liyuan et al 2013; Michael et al 2015 ), catalyze the covalent attachment of ubiquitin to substrates with the help of E1 (ubiquitin-activating enzyme) and E2 (ubiquitin-conjugating enzyme) proteins (Buetow and Huang 2016 ). A wide variety of ubiquitination processes participate in numerous biological pathways (Jmii and Cappadocia 2021 ; Wu et al 2021 ; Liu et al 2021 ; Uchida and Kitagawa 2016 ), and the predominant function, mediated by Lys48-linked ubiquitination, is to target proteins to the proteasome for degradation (Hiranyakorn et al 2020 ). Other types of linkages, e.g., Lys63-linkages, signal substrates for non-degradative functions, such as protein assembly or modification (Chen and Sun 2009 ) (Swatek and Komander 2016 ); or chromatin modelling or repair (Nakazawa et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%